Supermarket shopping and nutritional outcomes: A panel data analysis for urban Kenya - Demmler, Kathrin M.; Ecker, Olivier; Qaim, Matin (University of Göttingen, 2017)
Overweight and obesity are growing health problems in many developing countries. Rising obesity rates are the result of changes in people’s diets and lifestyles. Income growth and urbanization are factors that contribute to these changes. Modernizing food retail environments may also play a certain role. For instance, the rapid spread of supermarkets in many developing countries could affect consumer food choices and thus nutritional outcomes. However, concrete evidence about the effects of supermarkets on consumer diets and nutrition is thin. A few existing studies have analyzed related linkages with cross-sectional survey data. We add to this literature by using panel data from households and individuals in urban Kenya. Employing panel regression models with individual fixed effects and controlling for other factors we show that shopping in supermarkets significantly increases body mass index (BMI). We also analyze impact pathways. Shopping in supermarkets contributes to higher consumption of processed and highly processed foods and lower consumption of unprocessed foods. These results confirm that the retail environment affects people’s food choices and nutrition. However, the effects depend on the types of foods offered. Rather than thwarting modernization in the retail sector, policies that incentivize the sale of more healthy foods – such as fruits and vegetables – in supermarkets may be more promising to promote desirable nutritional outcomes.